EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMP IT IBNU SINA MERAUKE - Khoiri, Khoiri; Al Jauhari, Shofwan; Faisal, Faisal (ITB AAS Indonesia Surakarta, 2024)
This study focuses on discussing the effectiveness of using audio-visual learning media in improving student learning outcomes in PAI subjects at SMP IT Ibnu Sina Merauke. In accordance with the title that the author took, the type of research conducted by the author was field qualitative (Field Research). This type of qualitative field research (Field Research) is research that requires researchers to go to the field to make observations about a phenomenon in a natural state. By way of observation, interviews and documentation related to the problem to be studied. Field qualitative research conducted by the author aims to examine and determine the effectiveness of using audio-visual learning media in improving student learning outcomes in PAI subjects at SMP IT Ibnu Sina Merauke. After analyzing the conditions in the field, the results show that the learning process is carried out using audio-visual learning media at SMP IT Ibnu Sina Merauke, it is necessary to carry out several stages, namely: the preparation stage, the planning stage, the implementation stage and the evaluation stage. Then the factors that cause an increase in student learning outcomes by using audio-visual learning media, including: Facilities and infrastructure, teachers, students and the environment. Forms of using audio-visual learning media in improving student learning outcomes at SMP IT Ibnu Sina Merauke, use three forms, namely: forms of motivation, forms of information and forms of teaching. It can be said that the use of audio-visual learning media is very effective in improving student learning outcomes, especially in PAI subjects at SMP IT Ibnu Sina Merauke. As an implication of this research it is recommended that schools should provide facilities and infrastructure to support the learning process, especially audio-visual learning media. With this media, every learning, especially in PAI subjects, will be fun learning and produce the maximum expected achievement of learning objectives